Synthesis of new oxadiazole derivatives as α-glucosidase inhibitors. Issue 15 (1st August 2015) - Taha, Muhammad; Ismail, Nor Hadiani; Imran, Syahrul; Rokei, Muhammad Qamarruddin Bin; Saad, Syed Muhammad; Khan, Khalid Mohammed
Graphical abstract: Abstract: Oxadiazole derivatives (6 –28 ) having hydrazone linkage, were synthesized through condensation reaction between benzohydrazide 5 with various benzaldehydes. The oxadiazoles derivatives (6 –28 ) were evaluated for their α-glucosidase inhibitory activity. The IC50 values for inhibition activity vary in the range between 2.64 ± 0.05 and 460.14 ± 3.25 μM. The IC50 values were being compared to the standard acarbose (IC50 = 856.45 ± 5.60 μM) and it was found that compounds 6 –9, 12, 13, 16, 18, 20, 22 –28 were found to be more active than acarbose, while other compounds showed no activity. Structure–activity relationship (SAR) studies suggest that oxadiazole benzohydrazones (6 –28 ) inhibitory potential is dependent on substitution of the N -benzylidene part. Compound 18 (IC50 = 2.64 ± 0.05 μM), which has trihydroxy substitution at C-2′, C-4′, and C-5′ on N -benzylidene moiety, recorded the highest inhibition activity that is three-hundred times more active than the standard drug, acarbose (IC50 = 856.45 ± 5.60 μM). Compound 23 (IC50 = 34.64 ± 0.35 μM) was found to be the most active among compounds having single hydroxyl substitution. Shifting hydroxyl from C-2′ to C-4′ (6 ) and C-3′ (7 ) reduces inhibitory activity significantly. Compounds with chlorine substituent (compounds 16, 28, and 27 ) showed potent activities but lower as compared to hydroxyl analogs. Substituent like nitro or methyl groups at any position suppresses enzyme inhibition activity. This reveals the important presence of hydroxyl and halo groups to have enzyme inhibitory potential.